(untitled) (Sociologisk Forskning, 2000)
Rejoinder: The need for Sociologisk Forskning In this rejoinder, it is argued that there is still a need for a disciplinary journal for Swedish sociology. The authors agree upon the need to revitalise Sociologisk Forskning, but are critical to the proposal to transform it into a more popular scientific journal, with an aim to become a part of the general public debate. The internationalisation and specialisation of the Swedish sociological community have implied that sociological research, to a large degree, is carried out within subdisciplinary or interdiscipinary fields. Networks, journals, conferences have developed within these fields, which has led to the Swedish sociological association and Sociologisk Forskning loosing parts of their relevance. The authors suggest that the creation of a stationary editorial board, with professional competence and better economic opportunities, will raise the quality and intra-disciplinary relevance of the journal.